GASTRONOMI SASTRA DALAM NOVEL CANTIK ITU LUKA KARYA EKA KURNIAWAN - Januarti, Ulfah Dwi; Saputri, Dhini Yustia Widhyah (SINERGI : Jurnal Riset Ilmiah, 2025)
This study examines Eka Kurniawan’s novel Cantik Itu Luka through a literary gastronomy approach, which views food as a complex symbol in the representation of culture, power, and postcolonial identity. Using a qualitative method and a hermeneutic literary approach, the research analyzes the depiction of food and eating practices in the novel to uncover their symbolic, ideological, and historical meanings. The findings reveal that local foods such as tuna and sugarcane wine serve as symbols of resistance against colonial hegemony, while colonial foods like rijsttafel, wine, and biscuits reflect the legacy of domination still imprinted in collective memory. This analysis is supported by Bourdieu’s theory of habitus, Foucault’s concept of biopolitics, and Bhabha’s ideas of hybridity and colonial ambivalence. The study affirms that food in literary texts is not merely a narrative detail, but a crucial element for understanding power relations, historical trauma, and identity formation within the context of contemporary Indonesian literature.